PELAKSANAAN PROGRAM DESA MANDIRI PANGAN (PDMP) DI DESA KEPENUHAN HULU KECAMATAN KEPENUHAN HULU KABUPATEN ROKAN HULU - Alfikar "; Muhammad Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research is motivated by the program to handle the backward villages and rural food insecurity in Rokan Hulu by a decree of Rokan Hulu in 2011 . In this regard certainly drawn up plans to be realized . However , what has been planned that the results have not been able to reach the target . Fullness of the Upper Village is one of villages in a highly visible application of this program has not been implemented at all . There is only a stretch of paddy fields which no crop at all . Then , good cooperation between the government and the public has not created properly in terms of the implementation of this program . Coupled with the standards , orders and employment targets are not clear so people are reluctant to participate .The purpose of this study was to megetahui implementation of the planning process to determine the implementation of the Food Program Independent Village in the Upper Village Fullness why not go well . To find out what the barriers are affecting Independent Village Food Programme in the Fullness of the Upper Village that has not done well .The results of this study indicate that : 1 ) the implementation of the Independent Village Food Program have not been realized in accordance with the planned target . 2 ) obstacles on the ground such as land availability , budget , executive and public attitudes encountered in the implementation process can not be properly addressed by the government . 3 ) communication between the Government and Farmers as the executor has not been effective . 4 ) the structure and direction of the work is not yet clear as monitoring and implementing government has yet to convince the public that people are reluctant to participate in the implementation of this program .Keyword : development , agricultural development and implementation